Towards a Communication and Gender Epistemology: Possible [Re]articulations Among Noth Fields (2020)
The purpose of this article is to present a reflection on debate axes and possible articulations between the field of social communication and gender studies. To do this, it focuses on the question about the implementation of this emerging perspective in specific research processes, and in turn, in the irreducible challenges and tensions that its ethical, political and methodological dimension entails. Initially, there is a problematization of epistemological conditions and the scientific status of research in communication and gender, respectively, based on recognizing their radical questioning of instituted logics of knowledge production. Secondly, taking as reference the field experiences of our doctoral thesis, carried out on the one hand on the scenario of the women's prisons of the Province of Buenos Aires, and on the other in popular neighborhoods of Santiago del Estero -one of the poorest provinces of Argentina-, the methodological tensions and powers of the transdiscipline and intersection of these two fields are raised.